Account of synovial terminal nerve endings affects the clinical function of patients with chronic ankle instability: a retrospective cohort study - Xingyu Wang; Shengxuan Cao; Yungu Chen; Yun Bao; Chao Zhang; Xu Wang; Xin Ma (Bone & Joint Research, 2025)
Aims: Previous studies have reported synovial hypertrophy and synovitis in the ankle joint of patients with chronic ankle instability (CAI) and osteochondral lesion of the talus (OLT). The present study aimed to explore the correlation between pain level, clinical function of CAI patients with or without OLT, and the quantity of neurons and microvessels of synovium in the ankle joint. Methods: A total of 32 subjects (14 without OLT and 18 with OLT) were included. The Cumberland Ankle Instability Tool (CAIT), American Orthopaedic Foot and Ankle Society (AOFAS), and visual analogue scale (VAS)-pain score of every patient were assessed via questionnaire, and the quantity of their terminal nerve endings and microvessels in the stained synovium section were counted under microscope. Statistical analysis was conducted to determine surgical effects (arthroscopic Broström-Gould and bone marrow stimulation) and to evaluate the association between the quantity of terminal nerve endings and microvessels with function and pain level in the ankle joint. Results: No significant differences were found in demographics, clinical assessment, and concomitant intra-articular pathologies between the two groups (all p > 0.05). The CAIT, AOFAS, and VAS-pain (respectively at rest and at sport) scores of preoperative patients were significantly poorer than those of postoperative patients (all p < 0.01). Account of neurons was positively correlated with preoperative VAS in sport (r = 0.915, p < 0.001), and negatively correlated with preoperative CAIT (r = −0.677, p < 0.001), postoperative CAIT (r = −0.546, p = 0.001), and preoperative AOFAS (r = −0.615, p < 0.001). Conclusion: There were no significant differences, either pre- or postoperatively, between CAI patients and CAI with OLT patients in CAIT, AOFAS, and VAS-pain. The CAIT, AOFAS, and VAS-pain were markedly improved after arthroscopic treatment. The quantity of terminal nerve endings was positively correlated with pain level and negatively correlated with clinical function. Cite this article: Bone Joint Res 2025;14(7):609–618.